Comparative modeling and assessment of renewable hydrogen production and utilization in remote communities - Aydin, Muhammed Iberia; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study explores renewable energy transitions in remote communities by addressing the environmental and health impacts of fossil fuel dependency. Remote communities face unique challenges in terms of economic, social and cultural development because of their geographical isolation and limited access to infrastructure, resources and services. Considering Sandy Lake First Nation community in Ontario, Canada as a case study, a life cycle assessment investigation is comprehensively conducted to evaluate the environmental outcomes of implementing hydrogen-based renewable systems into community's infrastructure. The respective life cycle impact assessment studies are then carried out to compare the environmental impacts of different energy production methods. The results for Global Warming Potential (GWP) show 1.88 kg COQ eq./kWh for the diesel-only scenario, while the renewable-integrated scenarios result in ranges from 0.08 to 0.37 kg COQ eq./kWh. The results further show that renewable-integrated scenarios reduce global warming potential (GWP) by up to 98.7 %, compared to diesel-only systems. While renewable energy significantly lowers the most environmental indicators, the manufacturing of renewable and hydrogen technologies makes some contributions to ecotoxicity. The study findings emphasize the need for sustainable manufacturing, strategic policymaking, and incentives to accelerate renewable adoption in isolated settlements.
Keywords: Hydrogen; Fuels; Renewable energy; Life cycle assessment; Environmental impact; Remote communities; Computer Science; Engineering